Application of strategies to minimize the error in pathological anatomy - Helena Maria Vala Correia; Sónia Bernardo; Fernando Esteves; Carla Garcia (Instituto Politécnico de Viseu, 2017)
Introduction: increasingly, a correct clinical diagnosis in Veterinary Medicine presupposes an accomplishment of complementary diagnostic exams, including those from Pathological Anatomy specialty and the potential risks of jeopardizing the quality and reliability of the laboratory diagnosis should be appropriately identified to adopt procedures, aiming their minimization. Objetives: the objectives of this work include the categorization of errors related to the diagnostic technique that takes place in the Laboratory of Pathological Anatomy Veterinary and enumeration of strategies for minimizing frequent errors. Material and Methods: monitoring the routine histological technique, from the moment of entry and receipt of samples, to identify and record the most frequently observed errors. Results: the most frequently identified errors in this work included the incomplete filling or illegibility of the analysis request, followed by incorrect packaging of the sample, the inadequate amount of formaldehyde for fixation and transport of the sample, and the absence of indications to the correct orientation of the surgical specimen. Conclusion: the adoption of simple strategies, detailed in the present work, solves most of the detected pre-analytical errors and the adoption of an identification system for the samples can guarantee the analytical and post-analytical quality in the histopathological diagnosis, minimizing the errors.